Education on the Importance of Exclusive Breastfeeding for Babies In Suka Maju Village, Penarik District, Mukomuko Regency - Winda Amallia; Jalaria, Nova; Efrianti, Hammi; Noverita , Noverita; Diniarti , Fiya (Universitas Dehasen Bengkulu, 2025)
Exclusive breastfeeding is a condition where infants receive only breast milk from the mother without the addition of other liquids or solid foods, except for syrups containing vitamins, mineral supplements or drugs with the permission of a doctor. Based on the results of the 2024 Indonesian Nutrition Status Survey, the proportion of toddlers who received early breastfeeding initiation (IMD) in Bengkulu was 57.1%, while the proportion of infants aged 0-5 months receiving exclusive breastfeeding was 68.7%. In this article we discuss the activities of Dehasen University Bengkulu's Thematic Community Service Program (KKN-T) in 2025 which aims to improve community knowledge, awareness and behavior. The program is implemented through an educational approach, namely with the method of exclusive breastfeeding counseling, exclusive breastfeeding assistance visits and demonstration of oxytocin massage techniques and lactation massage using flip sheets and counseling kit props. This activity was carried out in collaboration with village officials and the local community. The results of the activity showed an increase in community awareness regarding the importance of exclusive breastfeeding. From the results of observations through the recapitulation of pre-test results there were 10 people (33.3%) who did not understand about exclusive breastfeeding, and after counseling and post-test observations there were 30 people (100%) who understood the importance of exclusive breastfeeding. This shows that the exclusive breastfeeding counseling program is quite effective as a community-based promotive and preventive strategy that can be a model of prevention.